Foundations of global communication - Hafez, Kai 1964-; Grüne, Anne; kinner, Alex (Abingdon, Oxon New York, NY Routledge, 2022)
This book provides a wide-ranging theoretical and empirical overview of the disparate achievements and shortcomings of global communication. This exceptionally ambitious and systematic project takes a critical perspective on the globalization of communication. Uniquely, it sets media globalization alongside a range of other globalized forms of communication, ranging from the individual to groups, civil society groupings, commercial enterprises and political formations. The result is a sophisticated and impressive overview of globalized communication across various facets. Moreover, the book does not merely provide a descriptive overview of these processes, but evaluates and assesses them for the extent to which they live up to the much-hyped claims of globalization's potential for creating a globally interdependent society. Covering all types of cross-border global communication in media, political and economic systems, civil societies, social media and lifeworlds of the individual, this unique book invaluable for students and researchers in media, communication, globalization and related areas"--
Theory of global communication -- Mass media and global public sphere -- Politics : the state's global communication -- Economy : global corporate communication -- Civil society and global movement communication -- Large communities : global online communication -- Small groups : global lifeworldly communication I -- The individual : global lifeworldly communication II -- Interdependencies of systems and lifeworlds -- Conclusion and future prospects.
Translation of: Grundlagen der globalen Kommunikation : Medien - Systeme - Lebenswelten.
Includes bibliographical references (265-312) and index (313-321)
Keywords: Communication, International